ARTIFICIAL INTELLIGENCE-BASED LEARNING MANAGEMENT IN MADRASAH: OPPORTUNITIES AND CHALLENGES - Jalaluddin Madani; Junaidi; Derysmono; Ahmad Rofiqi Tanzil; Siti Aniqoh Shofwani (Jurnal Ikhtibar Nusantara, 2026)
This study discusses Artificial Intelligence (AI)-based learning management in madrasah with a focus on its opportunities and challenges. The study aims to analyze the role of AI in planning, implementing, and evaluating learning, as well as in educational decision-making in madrasah. The method used is qualitative with a library research approach through the analysis of relevant literature. The results show that AI plays a role in improving teacher efficiency, supporting data-driven learning, and creating more adaptive and personalized learning processes. However, the implementation of AI also faces challenges such as limited infrastructure, low digital competence among educators, and issues of ethics and information validity. In conclusion, the integration of AI in madrasah needs to be balanced with strengthening the role of teachers and must remain grounded in Islamic educational values.